2018
DOI: 10.3758/s13414-017-1479-2
|View full text |Cite
|
Sign up to set email alerts
|

Intentional binding of visual effects

Abstract: When an action produces an effect, the effect is perceived earlier in time compared to a stimulus without preceding action. This temporal bias is called intentional binding (IB) and serves as an implicit measure of sense of agency. Typically, IB is investigated by presenting a rotating clock hand while participants execute an action and perceive a resulting tone. Participants are asked to estimate the time point of tone onset by referring to the clock hand position. This time point estimate is compared to a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
8
26
0
Order By: Relevance
“…The ANOVA indicated a significant effect of outcome delay on estimated-delay ratio (F(1.44, 47.61) = 5.69, p = 0.012, η 2 p = 0.147), although post-hoc tests showed no differences between all adjacent delay conditions (ps > 0.149). These results suggest that visual intentional binding can occur only when the action-outcome temporal discrepancy is smaller than 500 ms. Interestingly, this temporal limit of visual intentional binding was consistent with previous findings (Ebert & Wegner, 2010;Engbert et al, 2008;Ruess et al, 2018). Error bars denote standard error of the mean.…”
Section: Sense Of Agency In the Visual Domainsupporting
confidence: 91%
See 2 more Smart Citations
“…The ANOVA indicated a significant effect of outcome delay on estimated-delay ratio (F(1.44, 47.61) = 5.69, p = 0.012, η 2 p = 0.147), although post-hoc tests showed no differences between all adjacent delay conditions (ps > 0.149). These results suggest that visual intentional binding can occur only when the action-outcome temporal discrepancy is smaller than 500 ms. Interestingly, this temporal limit of visual intentional binding was consistent with previous findings (Ebert & Wegner, 2010;Engbert et al, 2008;Ruess et al, 2018). Error bars denote standard error of the mean.…”
Section: Sense Of Agency In the Visual Domainsupporting
confidence: 91%
“…It has been shown that visual feedback on action is able to induce sense of agency which can be modulated by temporal congruence between action and the feedback based on the comparator mechanism (Farrer, Bouchereau, Jeannerod, & Franck, 2008;Farrer et al, 2013;Franck et al, 2001;Imaizumi & Asai, 2017). Moreover, intentional binding has also been observed in the visual domain (Ebert & Wegner, 2010;Engbert et al, 2008), but can be weaker than in the auditory domain (Ruess et al, 2018). We expected that in this experiment, subjective ratings of agency over visual outcomes, similar to auditory outcomes, would be modulated by action-outcome temporal congruence (i.e., outcome delays).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This visual inferiority is consistent with previous findings on the other perceptual phenomena related to agency. For instance, the intentional binding effect, whereby subjective timings of voluntary action and its sensory outcome attract each other ((Haggard et al, 2002), also see Experiment 3), is weakened for a visual outcome relative to an auditory outcome (Ruess et al, 2018). Sensory attenuation, another agency-related perceptual modulation, whereby individuals are likely to perceive decreased intensity of sensory events caused by themselves, than by others or the environment, is robust in tactile (Blakemore et al, 1999) and auditory (Weiss, Herwig, & Schutz-Bosbach, 2011) domains, while "visual" attenuation is unlikely to occur (Schwarz, Pfister, Kluge, Weller, & Kunde, 2018).…”
Section: The Outcome In Modalitiesmentioning
confidence: 98%
“…Previous studies have included many actions, such as single key-pressing (e.g., Sato & Yasuda, 2005), continuous motor control (e.g., Knoblich & Kircher, 2004), or even gesturing (e.g., Daprati et al, 1997). Therefore, the sensory outcomes (e.g., sensory modalities, including vision or audition) depend on the action as the generator (Mifsud & Whitford, 2017;Ruess, Thomaschke, & Kiesel, 2018). Though previous studies have suggested that unnatural (Caspar, Cleeremans, & Haggard, 2015;Ebert & Wegner, 2010) c.f.…”
Section: Onset (Generation) Conditionmentioning
confidence: 99%